Teaching-Learning Strategies for Fostering Creative and Innovative Skills in Community School Students - Sigdel, Surya; Acharya, Bisna (Teacher Half-Yearly Journal, 2025)
This study examines the existing situations and practices of the strategies to promote creative and innovative skills in community schools. It also discusses the techniques to foster innovative teaching-learning activities based on students', teachers', and administrators’ understanding and experiences. Then, it explores the roles of the concerned authorities to support and empower the teachers to plan student-engaged activities and the students to perform their roles and grow with creative and innovative skills. A qualitative design was followed to complete this study, and the information for the study was collected from an open-ended questionnaire and in-depth interviews with the teachers, administrators, and students. The meaning was generated from the themes developed from the codes by categorizing and grouping the information gathered from the participants. The study found that the administration and management have a crucial role in establishing creative and innovative teaching-learning environments and facilitating the teachers to launch experiential teaching-learning activities. Similarly, when teachers guide the students to plan and conduct different curricular and co-curricular activities, they employ their best efforts and become more creative and innovative. It concludes that the activities planned and organized by the students under the guidance of the teachers and in support of the concerned authority make students more creative and innovative.